Experimental performance investigation of an active magnetic regenerator subject to different fluid flow waveforms. (February 2017) - Teyber, R.; Trevizoli, P.V.; Niknia, I.; Christiaanse, T.V.; Govindappa, P.; Rowe, A.
Highlights: A flow control device based on cam actuated valves is implemented on an AMR device. A no-flow period is used to increase the flow-averaged magnetic field change. The system is simulated to evaluate waveforms of constant displaced volume. AMR experiments are conducted and the performance of each waveform is discussed. Abstract: A flow control mechanism based on cam actuated valves is designed and implemented on an active magnetic regenerator test apparatus. The objective is to overcome the brief low field period of the nested concentric Halbach array by decreasing the fluid blow width, displacing fluid only when the magnetic field is close to the minimum and maximum values. Flow waveforms are simulated to evaluate varying blow durations with the same displaced volume. AMR experiments are performed where the largest Ex Q of 1.62 W is obtained with V D = 13.90 cm 3 and a diversion ratio of δ = 0.41, demonstrating an 11.2% increase over the sinusoidal waveform.